DINAMIKA PSIKOLOGIS YANG MENDORONG SESEORANG MELAKUKAN PEMBUNUHAN: STUDI KASUS PADA NARAPIDA DENGAN KASUS PEMBUNUHAN BERENCANA DI LEMBAGA PEMASYARAKATAN X - Putra, I Dewa Gede Udayana; Hartanti, Hartanti (Universitas Muhammadiyah Jember, 2020)
Every case of premeditated murder carried out by someone must be motivated by certain problems between the perpetrator and the victim that made the perpetrator plan the murder. The purpose of this study is to find out psychological dynamics such as what makes a person commit an act of murder. This study uses a case study method with a qualitative approach. Participants in this study amounted to one person, namely Agus (not real name), a prisoner in a premeditated murder case who was served a punishment at the X penitentiary .In the process, this study used observations, interviews and psychological testing tools that would help researchers in dynamizing participants. The results of this study indicate that Aguscommitted murder was motivated by feelings of jealousy towards his wife, poor coping, inconsistent parenting, bad living environment and imitative behavior make Acapable of killing.